Handwritten Newspapers An Alternative Medium during the Early Modern and Modern Periods - Droste, Heiko; Salmi-Niklander, Kirsti (Studia Fennica Historica, 2019)
"This book is the first edited volume focusing on handwritten newspapers as an alternative medium from a wide interdisciplinary and international perspective. Our primary focus is on handwritten newspapers as a social practice. The case studies contextualize the source materials in relation to political, cultural, literary, and economic history. The analysis reveals both continuity and change across the different forms and functions of the textual materials. In the 16th century, handwritten newspapers evolved as a news medium reporting history in the making. It was both a rather expensive public commodity and a gift exchanged in social relationships. Both functions appealed to public elites and their news consumption for about 300 years. From the late 18th century onwards, changing notions of publicness as well as the social needs of private or even secluded groups re-defined the medium. Handwritten newspapers turned more and more into an internal or even clandestine medium of communication. As such, it has served as a means to create social cohesion, political debate, and religious education for nonelite groups until the 20th century. Despite these changes, continuities can be observed both in the material layout of handwritten newspapers and the practices of distribution."